CD117 (c-Kit) Is Expressed During CD8+ T Cell Priming and Stratifies Sensitivity to Apoptosis According to Strength of TCR Engagement - Frumento, Guido; Zuo, Jianmin; Verma, Kriti; Croft, Wayne; Ramagiri, Pradeep; Chen, Frederick E.; Moss, Paul (Frontiers in Immunology, 2019)
CD117 (cKit) is the receptor for stem cell factor (SCF) and plays an important role in early haemopoiesis. We show that CD117 is also expressed following priming of mature human CD8+ T cells in vitro and is detectable following primary infection in vivo. CD117 expression is mediated through an intrinsic pathway and is suppressed by IL-12. Importantly, the extent of CD117 expression is inversely related to the strength of the activating stimulus and subsequent engagement with cell-bound SCF markedly increases susceptibility to apoptosis. CD117 is therefore likely to shape the pattern of CD8+ T cell immunodominance during a primary immune response by rendering cells with low avidity for antigen more prone to apoptosis. Furthermore, CD117+ T cells are highly sensitive to apoptosis mediated by galectin-1, a molecule commonly expressed within the tumour microenvironment, and expression may therefore represent a novel and potentially targetable mechanism of tumour immune evasion.